Visualizing Mineral-Associated Organic Matters in Long-Term Fertilization Treated Soils by NanoSIMS and SR-FTIR - Yu, Guang-Hui; Liu, Sha (Frontiers in Soil Science, 2022)
Formation of mineral-associated organic matters is essential for long-term soil organic carbon preservation. However, the regulation pathways of mineral-associated organic matters in soils remains largely undescribed, especially at the submicron scale. Using a well-controlled long-term (32 yrs) field experiment at the Jiangxi Institute of Red Soils, Jinxian, China, we showed that long-term manure fertilization significantly (P < 0.05) increased the available Al and Fe concentrations over one order of magnitude in soil water dispersible colloids compared to no fertilization and chemical fertilization. Nano-scale secondary ion mass spectrometry (NanoSIMS) images and region of interest (ROI) analysis provided direct evidence demonstrating that long-term manure fertilization increased the 27Al16O /12C-, 27Al16O /12C14N-, 56Fe16O /12C-, and 56Fe16O /12C14N- ratios compared to no fertilization and chemical fertilization, revealing that long-term manure fertilization may potentially enhance the stability of organic carbon and nitrogen. Synchrotron radiation based FTIR spectromicroscopy further supported that secondary oxides (< 950 cm-1) were co-localized with amines, lipids, and proteins in the long-term manure fertilization, but only co-localized with proteins in the no fertilization and chemical fertilization. To summarize, our findings highlight the importance of manure inputs in increasing formation of mineral-associated organic matters and thus potentially increasing soil carbon persistence.